Pairwise testing tools based on hill climbing algorithm (PTCA) - Lim, Seng Kee (2014)
Failure in software can cause serious damage and because of this it is essential to test the software thoroughly. Software testing is the activity to find the defects in the components or systems. The main problem in software testing is to test the system exhaustively as it is impossible to do so. To reduce the test cases generated during testing process, combinatorial algorithms which consisting Hill Climbing algorithm and T Way Combination algorithm as described in twayGenerator (Kamal Zuhairi Zamli, 2007) have been studied and reviewed. The actual implementation of the algorithm which is in Java programming language, the program is implemented on Net Bean 7.0.1. Assumptions have been made for the program. Several experiments were conducted included demonstrating the correctness of the algorithms, demonstrate PTCA successful in reducing test suite size, and benchmarking PTCA against existing strategies in order to prove PTCA achieved its objectives. Based on the experimental results, PTCA has successful in reducing the test size.